Incidence and determinants of nevirapine and efavirenz-related skin rashes in West Africans: nevirapine's epitaph? - Fred Stephen Sarfo; Maame Anima Sarfo; Betty Norman; Richard Phillips; David Chadwick (PLoS ONE)
Non-nucleoside reverse transcriptase inhibitor (NNRTI) associated rash is common and frequently leads to discontinuation of NNRTIs. This study assessed the risk of developing rashes and discontinuing NNRTIs and associated factors in a large clinic in central Ghana. In this retrospective cohort study, clinical data were obtained in patients starting efavirenz or nevirapine between 2004-2010. Factors associated with rashes were explored using a multivariate Cox proportional hazards regression model. Of 3,999 patients who started NNRTI-based ART, 281 (7.0%) experienced at least one episode of NNRTI-related rash with an incidence of 2.63 events/100 person-years, occurring in 10.2% and 5.6% of patients taking nevirapine and efavirenz respectively. Most rashes (94%) were grade 1 or 2 and were reported a median of 2 months following initiation of ART. In multivariate analysis developing a rash was associated with nevirapine use (aHR 1.67, 95% CI 1.28-2.10), female gender (aHR of 1.39, 95% CI 1.01-1.92) and lower baseline CD4 counts (aHR 0.88, 95% CI 0.82-0.95 per 50 cells/mm³ increment). Patients with nevirapine-associated rash were 11 times more likely to discontinue treatment as patients with efavirenz-associated rash. In contrast to findings in other studies, NNRTI-associated rashes in Ghanaians appear more common in patients with lower baseline CD4 counts. Given the increased frequency of rashes with nevirapine and subsequent discontinuations in many patients, along with other treatment-limiting toxicities, this provides further impetus for the replacement of nevirapine by efavirenz as the first-line NNRTI treatment of choice in Africa.